Self-esteem muslimah berbusana cadar dalam tinjauan psiko-ideologis - Titin Wulandari Lantong Rimba; Badi’uzzaman Sa’id Haqi (Seminar Nasional Bimbingan dan Konseling Jambore Konseling 3)
The issue of terrorism prevails over developed radicalism associated with Islamic faith. One of the indicatorsare using the veil (cadar) bymoslem woman. This paper present qualitatively to investigate the self-esteem of moslem woman who uses veil (cadar) in daily life. Through a psycho-ideological mind is known that the veil (cadar) which is used by them as the Islam implementation in concerning women. Related to the cases that often befall to the women dress and veil (cadar) allegedly has a relationship with the terrorism acts which always makes the people worried about. So that, the phenomenon which is happening infrequently coming to the women who wears veiled (cadar) getting an intimidation from the people and they beleive it. Related to the idea that the researchers want to investigate something related with the causes and reasons of Muslim women who wears veils (cadar), so there is no intimidation which experienced by the women who wears veil (cadar).